Pemberian Fusarium Non-Patogen dan Tricoderma Untuk Menghambat Penyakit Busuk Pangkal Pada Bawang Putih - Silvia Septhiani; Diah Oga Nusantari; Deni Nasir (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2018)
The need for garlic is quite high in Indonesia, but it is not offset by the amount of production. The decrease in production is caused by one of them by a base rot. This study was aim to determine the effect of the use of antagonistic fungi in overcoming base rot in garlic. The antagonistic fungi used are Trichoderma and non-pathogenic Fusarium. This research was conducted using a Completely Randomized Design (CRD) with 3 factors each with 2 treatment levels, resulting in 8 treatment combinations. The results showed that non-pathogenic Fusarium without integrated with other fungi reduced the symptoms of rotten tubers and increased the weight of fresh and weighted tubers. The integration of pathogen and non-pathogen Fusarium, also Trichoderma can reduce the symptoms of base rot.